ADVANTAGE OF EARLY LOCALIZATION IMAGING STUDIES IN PATIENTS WITH NORMOCALCEMIC HYPERPARATHYROIDISM - Hoang, Thanh; Hatfield, Jennifer; Shakir , Mohamed (Journal of the ASEAN Federation of Endocrine Societies, 2022)
OBJECTIVES Currently, there is no clear evidence regarding the benefits of surgery for patients with normocalcemic hyperparathyroidism (NC-HPT). The goal of this study was to determine the usefulness of imaging to guide surgical treatment in patients with NC-PHPT. METHODOLOGY This is a retrospective study that included 221 patients with hyperparathyroidism seen during 2004-2020. Laboratory and imaging studies were performed at our hospital. RESULTS Of the 221 patients, only eight (3.6%) patients met the criteria for NC-HPT. The majority were female, aged between 42 to 82 years, with PTH levels ranging from 78 to 380 pg/mL. All patients were normocalcemic (9.8 to 10.3 mg/dL). Two patients had a history of nephrolithiasis. Only one patient had nonspecific fatigue as a symptom, while the rest were asymptomatic. DXA scan done showed that three patients had osteoporosis and three had osteopenia. On neck ultrasound, only two patients had parathyroid findings. However, on Sestamibi parathyroid scan, four patients had tracer localization. Three patients underwent parathyroidectomy with histopathological confirmation of adenomas ranging from 120 to 261 mg in weight (normal 20-40 mg). CONCLUSION In patients with NC-HPT, medical therapy such as cinacalcet is not indicated. Although it has been suggested that NC- HPT may represent an early stage of PHPT, complications like osteoporosis and nephrolithiasis may still occur. Prompt and timely imaging studies in this subset of patients may facilitate early surgical treatment if warranted. Subsequently, the occurrence of hyperparathyroidism- related complications may be prevented.